استدامة تنمية مهارات الاتصال الفعال من منظور تبني استراتيجية التشارك المعرفي: بحث تحليلي في المعهد التقني /البصرة - Al-Salman م.م. حسام عبدالامير محمد; Hashim ا.د. هاشم نايف; Salman م.م. حامد شاكر محمود (Tasnim International Journal for Human, Social and Legal Sciences, 2022)
The research aims to identify and analyse the different roles of knowledge sharing in ways to enhance effective communication skills in the surveyed community. As the research problem was represented by the main question, what is the role of knowledge sharing in achieving sustainable development of effective communication skills? As embodied in the importance of research in contributing to the deepening of scientific knowledge of the variables of the research understudy, the Technical Institute at the Southern Technical University in Basra Governorate was elected as a field to measure the scheme and hypotheses of the research, and the descriptive-analytical method was used, while the sample was intended to target the teachers at the institute. Using the SPSS.V.25 program to analyse the collected data. The research concluded that the communication that takes place through speaking (speaking skill) is one of the best means of communication that can be used within the surveyed community and that the communication that takes place through writing (writing skill) is Effective, but its negatives stand against the wheel of speed, in addition to being subjected to some harassment or distortions that are affecting the credibility of what is written. The research concluded with many recommendations, the most important of which were: The need to rearrange the priorities of the senior management (dean and heads of departments) concerning developing and improving effective communication skills between Faculty members with each other, between faculty members, and among individuals working in the community in question through building a knowledge sharing strategy so that it can contribute to creating an internal environment It is characterized by harmony and compatibility, as well as organizing group meetings for discussion and dialogue, exchanging ideas, information and knowledge and transmitting them to others.